2016
DOI: 10.1016/j.vaccine.2016.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Brief education to promote maternal influenza vaccine uptake: A randomized controlled trial

Abstract: www.clinicaltrials.gov (NCT01772901).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 54 publications
(75 reference statements)
1
37
0
Order By: Relevance
“…Specifically, of the 40% that received a recommendation and an offer of influenza vaccination, 95% were vaccinated; however, among those who received neither a vaccination recommendation nor an offer, only 5% were vaccinated. This finding supports the literature that healthcare provider recommendation and offer of influenza vaccination are leading predictors of vaccination among pregnant women [612] and substantiates that healthcare providers with up-to-date knowledge, good practices and attitudes towards influenza vaccination foster acceptance of the vaccine among pregnant women [13,14]. …”
Section: Discussionsupporting
confidence: 85%
“…Specifically, of the 40% that received a recommendation and an offer of influenza vaccination, 95% were vaccinated; however, among those who received neither a vaccination recommendation nor an offer, only 5% were vaccinated. This finding supports the literature that healthcare provider recommendation and offer of influenza vaccination are leading predictors of vaccination among pregnant women [612] and substantiates that healthcare providers with up-to-date knowledge, good practices and attitudes towards influenza vaccination foster acceptance of the vaccine among pregnant women [13,14]. …”
Section: Discussionsupporting
confidence: 85%
“…Of the nine RCTs, three were assessed as 'strong' [28,29,30], three 'moderate' [31,32,33] and three 'weak' [34,35,36] in quality. The weak-quality studies had methodological flaws with allocation concealment, blinding and power.…”
Section: Randomised Control Trialsmentioning
confidence: 99%
“…Information and education was important for both staff and patients separately. Information for patients was found to be effective at increasing vaccine coverage when administered through education sessions, posters or pamphlets [30,32,38,40].…”
Section: Information and Education For Patientsmentioning
confidence: 99%
“…Pregnant women are a priority group for vaccination, but vaccination rates among this risk group are reportedly low in the EMR (7). A randomized clinical trial revealed that brief one-on-one education of pregnant women on vaccine safety and availability as well as the potential complications from influenza substantially improved vaccine acceptance and coverage in this risk group (15). This type of advocacy and education is likely to prove effective among other risk groups.…”
mentioning
confidence: 99%